2020
DOI: 10.31590/ejosat.779952
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Veri Kümesinin SMOTE Tabanlı Örnekleme Yöntemi Uygulanarak Sınıflandırılması

Abstract: Öz Son yıllarda dengesiz tıbbi veri kümeleri üzerinde gerçekleştirilen öğrenme problemine verilen önem artmaktadır. Çünkü gerçek yaşamda karşılaşılan tıbbi veri kümeleri sıklıkla dengesiz veri kümeleridir. Sınıflandırıcıların dengesiz ortamdaki davranışlarını inceleyen pek çok çalışma, başarım değerlerindeki önemli kaybın veri kümelerinde oluşan çarpık sınıf dağılımından kaynaklandığını vurgulamıştır. Literatürde, bu çarpıklık sorununu çözmek için Sentetik Azınlık Örneklem Arttırma Yöntemi (SMOTE) algoritması … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
0
9
0
3
Order By: Relevance
“…In a study, it was tried to predict Covid-19 patients based on laboratory test results commonly collected from suspected Covid-19 case applications using the Synthetic Minority Sampling Method (SMOTE) and Artificial Neural Networks (ANN) algorithm. As a result of the study, the success rate was found to be 86% in the original data set, while it was observed that the success rate increased to 90% when the unbalanced data distribution was eliminated by using the SMOTE-based method [7]. It has also been observed that studies have been conducted to estimate the number of cases using machine learning methods [8].…”
Section: Introductionmentioning
confidence: 91%
“…In a study, it was tried to predict Covid-19 patients based on laboratory test results commonly collected from suspected Covid-19 case applications using the Synthetic Minority Sampling Method (SMOTE) and Artificial Neural Networks (ANN) algorithm. As a result of the study, the success rate was found to be 86% in the original data set, while it was observed that the success rate increased to 90% when the unbalanced data distribution was eliminated by using the SMOTE-based method [7]. It has also been observed that studies have been conducted to estimate the number of cases using machine learning methods [8].…”
Section: Introductionmentioning
confidence: 91%
“…In this study, the dataset [22], which consists of Chest X-Ray images, has been used. This dataset is a collection of the different datasets from different studies [23,24]. In the dataset 1 , there are 1341 normal/healthy X-Rays, 1345 virus pneumonia X-Rays, and 219 Covid-19 X-Rays.…”
Section: The Datasetmentioning
confidence: 99%
“…SMOTE tekniği, bu gibi durumlarda en yaygın kullanılan ve çoğu zaman en başarılı örnekleme yöntemi olarak literatürde yer almaktadır. Algoritmanın çalışma mantığı Şekil 1'de gösterildiği gibidir [6]. Burada öncelikle, azınlık sınıfına ait her bir gözlemin en yakın k komşusu aranır.…”
Section: B Smote (Senteti̇k Azinlik öRneklem Arttirma Yöntemi̇)unclassified
“…Son yıllarda dengesiz veri kümelerinde, dengesiz veri gruplarını artırmak ya da veri sayısı az olan ve veri toplamanın zor olduğu konularda sentetik olarak veri üretmek amacıyla kullanılan yöntemlerden birisi de SMOTE olmuştur. Literatürde yapılan çalışmalar incelendiğinde, Yavaş ve arkadaşları [6] Covid-19 hastalığının teşhisinde yapay sinir ağı modelinin başarım oranını arttırmak için SMOTE yöntemini önermişlerdir. Çalışmada kullanılan model ile 0.86 olarak elde edilen doğruluk değeri, SMOTE kullanılarak dengelenen veri kümesinde 0.90'a çıkmıştır.…”
Section: Introductionunclassified